PEDIATRIC TUBERCULOSIS IN THE NORTH SARDINIA - Maria Grazia Clemente; Elena Dore; Lidia Abis; Paola Molicotti; Stefania Zanetti; Paolina Olmeo; Roberto Antonucci (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objectives: Migration flux is an increasing phenomenon in Italy, and it raises several public health issues and concerns in pediatric infectious diseases. This study investigated the clinical characteristics and outcomes of a pediatric population at high-risk for tuberculosis (TB) and the potential role of immigration as a risk factor.